2008
DOI: 10.1002/j.2050-0416.2008.tb00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Sake and Beer Spoilage Lactic Acid Bacteria - A Review

Abstract: Japanese rice wine, sake, is a traditional alcoholic beverage in Japan. Similar to the case with beer, sake is known to be microbiologically stable and most microorganisms fail to grow in sake. This is principally due to its high ethanol concentration that reaches approximately 20% (v/v) in undiluted sake products and 15% (v/v) in finished products. Despite the high level of ethanol content, spoilage incidents occasionally occur in sake, due to the presence of highly ethanol-tolerant lactobacilli, known as hio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
96
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 103 publications
0
96
0
4
Order By: Relevance
“…Most Pectinatus species have been isolated from beer and brewery environments but their natural environment and source of contamination are not well understood [89]. It has been found that several sources of contamination can be identified in the same brewery.…”
Section: Pectinatusmentioning
confidence: 99%
“…Most Pectinatus species have been isolated from beer and brewery environments but their natural environment and source of contamination are not well understood [89]. It has been found that several sources of contamination can be identified in the same brewery.…”
Section: Pectinatusmentioning
confidence: 99%
“…L. brevis has been implicated in more than half of beer spoilage incidents within the same period 3,6,21 while a further 15-20% have been caused by L. lindneri 2,6 . L. coryniformis, L. casei and L. plantarum are other important Lactobacillus species which have been reported to spoil beer 6,38 with a frequency of beer spoilage incidents of 3, 2 and 1% respectively 2,47,48 . Lactobacillus species cause high turbidity, hazy appearance, unpleasant flavours and a high level of diacetyl in beer 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Gram positive beer spoilage bacteria include several species of lactic acid bacteria (LAB), which are reported as the most hazardous bacteria for breweries as they are responsible for approximately 70% of all microbial spoilage incidents 3,31 . Indeed, LAB can be found in brewing materials at almost every stage of the malting and brewing process, from the standing barley crop to the finished beverage 13,17,28,33 . These bacteria occur as part of the natural barley micro-biota, and persist during malting and mashing 29,35 due to their aero tolerant nature and tolerance of low pH and high ethanol levels.…”
Section: Introductionmentioning
confidence: 99%
“…Among them the most important spoilage organisms are, according to brewing literature, L. brevis, L. lindneri, L. paracollinoides and P. damnosus 2,30,32,34 . In addition, L. backi and P. inopinatus have been reported as potential beer spoilers 7,22,33 . A recently characterised strain, P. clausseni, has been shown to spoil beer 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation